Artificial Development by Reinforcement Learning Can Benefit From Multiple Motivations - Palm, Günther; Schwenker, Friedhelm (Frontiers in Robotics and AI, 2019)
Research on artificial development, reinforcement learning, and intrinsic motivations like curiosity could profit from the recently developed framework of multi-objective reinforcement learning. The combination of these ideas may lead to more realistic artificial models for life-long learning and goal directed behavior in animals and humans.